Effect of stress on sleep quality in young adult medical students: a cross sectional study - Lohitashwa, Renu; Kadli, Ningamma; Kisan, Ravikiran; A, Sindhuja; Deshpande, Dileep (International Journal of Research in Medical Sciences, 2017)
Background: Because of demanding clinical and academic duties, medical students are at an increased risk for development of sleep disruption. Studying the relation between sleep quality and psychological stress can be useful in implementing an organized mental health program in medical colleges. The main objective is to study the prevalence and the effect of stress on sleep quality in young adult medical students. Methods: A cross sectional study to recognize the effect of stress on sleep quality among 50 medical students. The instruments used for data collection were a self-report Pittsburg Sleep Quality Index (PSQI) and the General Health Questionnaire (GHQ). Results: Results of present study showed that 58% of subjects were poor sleepers. Furthermore, there was a significant correlation between general health status and sleep quality of students (r = 0.5118, p = 0.0001). Conclusions: A considerable proportion of medical students are affected by poor sleep quality. Sleep disruption acts as a barrier for students’ performance in examinations. So, it is important to implement health promotion and educational programs for them.